Effectiveness of a Multifactor Educational Intervention on Delirium Incidence and Length of Stay in Patients with Cardiac Surgery - Ali Bavi; Khadijeh Biat; Shadan Pedram Razi; Mohamad Arbabi; Mitra Zolfaghari (Tehran University of Medical Sciences, 2012)
Background & Aim: Delirium is a common problem among patients with open heart surgery admitted to intensive care units. This study aimed to assess effectiveness of a multifactor intervention on delirium prevention and length of stay in patients with open heart surgery. Methods & Materials: In this semi-experimental study, we first recruited 195 patients. Among them, 15 patients were excluded during the study due to different reasons. The participants were divided into to study groups. The implemented intervention included staff education, environment changes, and installation of guideline reminding on ward. Patients were assessed for delirium twice a day using the CAM-ICU scale. Demographic characteristics as well as disease and sleep items were completed by the researchers a day before surgery. Moreover, length of stay was recorded by the researchers. Data were analyzed using Pearson Chi-Square, Independent Samples, and the Fisher's Exact Test. Results: A significant decrease was found in the incidence of delirium in the intervention group: 11.1% Vs 35.6% (P<0.05). Average length of stay in the control and intervention groups was 6.23 Vs 6.30 days, respectively. Length of stay among patients with delirium and patients without delirium was 7.5 Vs 5.8 days, respectively. Patients with delirium were aged 55 and more in both groups. Conclusion: Multifactor intervention was effective in decreasing the prevalence of delirium. Educational interventions are recommended to improve staffs' knowledge and environment changes.